Numerical study on heat transfer and lubricant depletion in a heat assisted magnetic recording system with multilayer disk structure - Zeng, Yan (2013)
Heat transfer and lubricant depletion in a HAMR system with multilayer disk substrate are numerically simulated in this study. Cases under two types of multilayer disk substrates with different materials on the top layer as well as different laser powers are examined. The results show the significant effects of the material property and the laser power. Compared with pure glass disk substrate, larger thermal conductivity of top-layer material in the multilayer disk substrate causes faster heat conduction and thus substantial reductions in the temperature increase and lubricant depletion on the top surface. Hence it is necessary and important to incorporate the real multilayer structure in modeling heat transfer and lubricant depletion in practical HAMR systems.